A graphene suspension and a preparation method thereof, and a graphene-enhanced tellurium-copper composite material and a preparation method thereof
The graphene suspension was prepared by ultrasonic peeling and synthesized with copper tellurium powder, which solved the poor dispersion and complex preparation problems of graphene and copper tellurium when composited with copper tellurium, and significantly improved the mechanical and electrical properties of the composite material.
Patent Information
- Application Number
- CN202411930457.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
The existing graphene and copper tellurium materials have problems such as poor dispersion, complex preparation process and high energy consumption when composited with copper tellurium, which leads to the inability to effectively improve the mechanical and electrical properties of copper tellurium tellurium.
By mixing scale graphite, nano copper oxide and solvent and then performing ultrasonic peeling, a high-quality graphene suspension was prepared, and then mixed with copper tellurium powder was heat reduction, pressing, sintering and extruding to prepare a graphene-reinforced copper tellurium composite material.
The conductivity, tensile strength and limit current breaking times of graphene-reinforced tellurium copper composite material have been significantly improved, especially the increase of tensile strength and limit current breaking times is very large.
Smart Images

Figure BDA0005210157750000081 
Figure BDA0005210157750000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrical materials, and in particular to a graphene suspension and a preparation method thereof, and a graphene-enhanced tellurium-copper composite material and a preparation method thereof. Background Art
[0002] Tellurium copper alloy materials have good electrical and thermal conductivity, as well as certain corrosion resistance and electrical ablation resistance. They are mainly used for electrical contacts that require high conductivity. In recent years, they have been widely used as contact materials for high-voltage DC relays for new energy vehicles. With the progress of society, the increase in voltage and current of high-voltage DC relays for new energy vehicles requires contact materials to have higher strength and conductivity, and more reliable anti-welding ability. Tellurium copper contacts can no longer meet the requirements of electrical appliances.
[0003] Graphene is a two-dimensional material with ultra-high strength, good electrical and thermal conductivity that has been discovered so far. It is regarded as an excellent reinforcement phase for metal-based composite materials. Single-layer and few-layer high-quality graphene with complete structure and few defects is the key to achieving excellent reinforcement effect. The reported graphene preparation methods can be summarized into three categories: ① mechanical exfoliation, ② growth on a support surface, and ③ wet chemical method. Among these three methods, the graphene prepared by mechanical exfoliation has the least defects and the highest quality. The carbon atoms in graphite form σ bonds with sp2 hybrid orbitals and delocalized π bonds with Pz orbitals. These bonds combine to form a strong hexagonal grid-like plane with a bond energy of 345KJ / mol. The bonding force between the layers of graphite is weak, and they are mainly connected by van der Waals forces with a bond energy of 16.7KJ / mol. This leads to the disadvantages of poor dispersion, complex preparation process and high energy consumption in the composite of graphene and copper telluride materials, which seriously affects the improvement of the mechanical and electrical properties of copper telluride materials by graphene.
[0004] Therefore, how to obtain high-quality single-layer and few-layer graphene to improve the mechanical and electrical properties of tellurium copper alloy materials has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a graphene suspension and a preparation method thereof and a graphene-enhanced tellurium-copper composite material and a preparation method thereof. The mechanical properties and electrical properties of the graphene-enhanced tellurium-copper composite material prepared by using the graphene suspension provided by the present invention are significantly improved.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a method for preparing a graphene suspension, comprising: mixing flake graphite, nano copper oxide and a solvent, and then performing ultrasonic peeling to obtain a graphene suspension;
[0008] The average particle size of the nano copper oxide is 1 to 50 nm.
[0009] Preferably, the average particle size of the flake graphite is 0.5 to 20 μm.
[0010] Preferably, the solvent is NMP.
[0011] Preferably, the mass ratio of the flake graphite, nano copper oxide and solvent is 1:(5-10):(80-120).
[0012] The present invention provides a graphene suspension prepared by the preparation method described in the above technical solution.
[0013] The present invention provides a method for preparing a graphene-reinforced tellurium-copper composite material, comprising the following steps:
[0014] (1) mixing tellurium copper powder, ethanol and a graphene suspension to obtain a mixture; the graphene suspension is a graphene suspension prepared by the preparation method described in the above technical solution;
[0015] (2) subjecting the mixture obtained in step (1) to thermal reduction to obtain a mixed powder;
[0016] (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material.
[0017] Preferably, in the step (1), the mass percentage of tellurium in the tellurium copper powder is 0.1-1%, and the average particle size of the tellurium copper powder is 10-40 μm.
[0018] Preferably, in step (1), the mass ratio of tellurium copper powder, ethanol and graphene suspension is (4-10):2:1.
[0019] Preferably, in step (2), the temperature of the thermal reduction is 280-320° C., the time of the thermal reduction is 2-4 hours, and the atmosphere of the thermal reduction is hydrogen.
[0020] The present invention provides a graphene-reinforced tellurium-copper composite material prepared by the preparation method described in the above technical solution.
[0021] The present invention provides a method for preparing a graphene suspension, comprising: mixing flake graphite, nano copper oxide and a solvent, and then performing ultrasonic exfoliation to obtain a graphene suspension; the average particle size of the nano copper oxide is 1 to 50 nm. The present invention adds nano copper oxide during ultrasonic exfoliation, and flake graphite forms a suspension with the solvent and nano copper oxide, and utilizes the cavitation effect of the ultrasonic process to realize liquid-solid phase exfoliation of graphene. Since the size of nano copper oxide is very small, it will not cause serious damage to graphene during the impact on graphite, but only open the interlayer van der Waals force, ensuring that the exfoliation process is only carried out between graphene layers, thereby obtaining high-quality single-layer and few-layer graphene suspensions; at the same time, nano copper oxide can be reduced to copper when preparing tellurium copper composite materials, and other metal impurities will not be introduced, thereby improving the purity of the tellurium copper composite materials. The results of the examples show that the conductivity of the graphene-enhanced tellurium-copper composite material prepared by using the graphene suspension provided by the present invention is ≥93.0% IACS, the tensile strength is >380 MPa, and the limiting current breaking number is >50 times, wherein the tensile strength and the limiting current breaking number are greatly improved, indicating that the graphene suspension provided by the present invention can improve the mechanical properties and electrical properties of the graphene-enhanced tellurium-copper composite material. DETAILED DESCRIPTION
[0022] The invention provides a method for preparing a graphene suspension, comprising: mixing flake graphite, nano copper oxide and a solvent, and then performing ultrasonic peeling to obtain a graphene suspension;
[0023] The average particle size of the nano copper oxide is 1 to 50 nm.
[0024] In the present invention, unless otherwise specified, the specific sources of the raw materials used are not particularly limited, and commercially available products well known to those skilled in the art may be used.
[0025] In the present invention, the average particle size of the flake graphite is preferably 0.5 to 20 μm. The present invention is conducive to better ultrasonic exfoliation of nano copper oxide by controlling the average particle size of the flake graphite. As an embodiment of the present invention, the average particle size of the flake graphite can be 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm.
[0026] In the present invention, the average particle size of the nano copper oxide is 1 to 50 nm. The present invention can further improve the peeling effect by using nano copper oxide to peel off graphene; by controlling the average particle size of nano copper oxide, the nano copper oxide will not cause serious damage to the graphene during the impact with the flake graphite, but only open the interlayer van der Waals force, ensuring that the peeling process is only carried out between the graphene layers, thereby obtaining high-quality single-layer and few-layer graphene; in addition, nano copper oxide can be reduced to copper when preparing tellurium copper composite materials, and other metal impurities will not be introduced, thereby improving the purity of the tellurium copper composite materials. As an embodiment of the present invention, the particle size of the nano copper oxide can be 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm.
[0027] In the present invention, the solvent is preferably NMP (N-methylpyrrolidone). By selecting NMP, the present invention can play a good protective role on the flake graphite during the ultrasonic stripping process, thereby ensuring that only the interlayer van der Waals force is opened, so that the stripping process is carried out between the graphene layers, thereby improving the quality of single-layer and few-layer graphene.
[0028] In the present invention, the mass ratio of the flake graphite, nano copper oxide and solvent is preferably 1: (5-10): (80-120). The present invention can further improve the effect of liquid-solid phase exfoliation of graphene by controlling the dosage relationship of each component. As an embodiment of the present invention, the mass ratio of the flake graphite, nano copper oxide and solvent can be 1: (6-9): (90-110), or 1: (7-8): 100.
[0029] In the present invention, the power of the ultrasonic peeling is preferably 150 to 750 W; the time of the ultrasonic peeling is preferably 4 to 12 hours. The present invention can further improve the peeling effect by controlling the process parameters of the ultrasonic peeling. As an embodiment of the present invention, the power of the ultrasonic peeling can be 300 to 600 W, or 400 to 500 W; the time of the ultrasonic peeling can be 6 to 10 hours, or 7 to 8 hours.
[0030] The invention adds nano copper oxide during ultrasonic stripping, forms a suspension of flake graphite, a solvent and the nano copper oxide, and utilizes the cavitation effect of the ultrasonic process to realize liquid-solid phase stripping of graphene. Since the size of the nano copper oxide is very small, the graphene will not be seriously damaged during the impact process on the graphite, but only the van der Waals force between the layers is opened, so that the stripping process is only carried out between the graphene layers, thereby obtaining a high-quality single-layer and few-layer graphene suspension; at the same time, the nano copper oxide can be reduced to copper when preparing the tellurium copper composite material, and other metal impurities will not be introduced, thereby improving the purity of the tellurium copper composite material.
[0031] The present invention also provides a graphene suspension prepared by the preparation method described in the above technical solution.
[0032] In the present invention, the mass ratio of graphene, nano copper oxide and solvent in the graphene suspension is preferably 1: (5-10): (80-120). As an embodiment of the present invention, the mass ratio of graphene, nano copper oxide and solvent can be 1: (6-9): (90-110), or 1: (7-8): 100.
[0033] In the present invention, the graphene in the graphene suspension includes single-layer graphene and few-layer graphene. The present invention has no special limitation on the mass relationship between the single-layer graphene and the few-layer graphene, and any graphene obtained by ultrasonic peeling can be used.
[0034] The present invention also provides a method for preparing a graphene-enhanced tellurium-copper composite material, comprising the following steps:
[0035] (1) mixing tellurium copper powder, ethanol and a graphene suspension to obtain a mixture; the graphene suspension is a graphene suspension prepared by the preparation method described in the above technical solution;
[0036] (2) subjecting the mixture obtained in step (1) to thermal reduction to obtain a mixed powder;
[0037] (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material.
[0038] The invention mixes tellurium copper powder, ethanol and graphene suspension to obtain a mixture.
[0039] In the present invention, the mass percentage of tellurium in the tellurium copper powder is preferably 0.1-1%; the average particle size of the tellurium copper powder is preferably 10-40 μm. By adopting the above-mentioned tellurium copper powder, the present invention can further improve the density of the graphene-enhanced tellurium copper composite material, thereby improving its mechanical properties and electrical properties. As an embodiment of the present invention, the mass percentage of tellurium in the tellurium copper powder can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; the average particle size of the tellurium copper powder can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0040] In the present invention, the mass ratio of the tellurium copper powder, ethanol and graphene suspension is preferably (4-10):2:1, more preferably (5-9):2:1, and further preferably (6-8):2:1. The present invention can control the amount of graphene in the tellurium copper powder by controlling the amount relationship of the tellurium copper powder, ethanol and graphene suspension, thereby further improving the mechanical properties and electrical properties of the graphene-reinforced tellurium copper composite material.
[0041] In the present invention, the copper telluride powder, ethanol and graphene suspension are preferably mixed by stirring; the mixing time is preferably 1 to 2 hours; and the stirring speed is preferably 100 to 300 r / min. The present invention can make the components mix evenly by controlling the stirring parameters. As an embodiment of the present invention, the mixing time can be 1.5 hours; the stirring speed can be 150 to 250 r / min, and can also be 200 r / min.
[0042] After obtaining the mixture, the present invention performs thermal reduction on the mixture to obtain mixed powder.
[0043] In the present invention, the temperature of the thermal reduction is preferably 280-320°C; the time of the thermal reduction is preferably 2-4 hours; and the atmosphere of the thermal reduction is preferably hydrogen. The present invention can reduce the oxygen content in the mixture through thermal reduction, reduce the nano copper oxide to copper, and lay the foundation for the subsequent preparation of high-performance tellurium copper composite materials. As an embodiment of the present invention, the temperature of the thermal reduction can be 290-310°C, or 300°C; the time of the thermal reduction can be 2.5-3.5 hours, or 3 hours.
[0044] After the thermal reduction is completed, the present invention preferably cools the thermally reduced product to obtain a mixed powder. In the present invention, the cooling atmosphere is preferably nitrogen or an inert atmosphere; the inert atmosphere is preferably argon or helium. The present invention can avoid re-oxidation of the mixed powder by cooling in a nitrogen atmosphere or an inert atmosphere. The present invention does not have any special limitation on the cooling rate, which can be determined according to the technical common sense of those skilled in the art. As an embodiment of the present invention, the cooling method can be natural cooling or furnace cooling.
[0045] After obtaining the mixed powder, the present invention sequentially presses, sinters and extrude the mixed powder to obtain a graphene-reinforced tellurium-copper composite material.
[0046] In the present invention, the pressing method is preferably cold isostatic pressing; the pressing pressure is preferably 250-400 MPa. The present invention has no special limitation on the pressing time, which can be determined according to the technical common sense of those skilled in the art. The present invention can press the mixed powder into a green body through pressing, which is convenient for subsequent sintering. As an embodiment of the present invention, the pressing pressure can be 300-350 MPa; the pressing time can be 30-60 s, or 40-50 s.
[0047] In the present invention, the sintering temperature is preferably 950-1080°C; the sintering time is preferably 2-5h; the sintering atmosphere is preferably nitrogen or an inert atmosphere; the inert atmosphere is preferably argon or helium. The present invention can further improve the density of the tellurium copper composite material by controlling the sintering temperature and time. As an embodiment of the present invention, the sintering temperature can be 980-1050°C, or 1000-1020°C; the sintering time can be 3-4h. The present invention does not have any special limitation on the cooling method of the sintering, and both natural cooling and furnace cooling are possible.
[0048] In the present invention, the extrusion temperature is preferably 700-950°C; the extrusion ratio is preferably 30-150; and the extrusion atmosphere is preferably nitrogen. The present invention can further improve the compactness of the tellurium copper composite material by hot extrusion, thereby improving the mechanical properties and electrical properties of the tellurium copper composite material. As an embodiment of the present invention, the extrusion temperature can be 750-900°C, or 800-850°C; the extrusion ratio can be 50-120, or 80-100.
[0049] The invention uniformly mixes the graphene suspension and the tellurium copper powder, performs low-temperature liquid phase volatilization and nano copper oxide reduction, obtains uniformly mixed graphene-tellurium copper mixed powder, and then performs pressure processing and heat processing to obtain high-quality graphene reinforced tellurium copper composite material. The preparation method provided by the invention is simple, can be prepared by existing equipment, does not need to introduce new equipment, and has low energy consumption, reduces production costs, improves the market competitiveness of products, and is conducive to large-scale industrial promotion.
[0050] The present invention also provides a graphene-reinforced tellurium-copper composite material prepared by the preparation method described in the above technical solution.
[0051] The graphene-enhanced tellurium-copper composite material provided by the invention has excellent mechanical properties and electrical properties.
[0052] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] A method for preparing a graphene suspension comprises: mixing flake graphite, nano copper oxide and a solvent, and then performing ultrasonic exfoliation at a power of 500 W for 4 hours to obtain a graphene suspension;
[0055] The average particle size of the nano copper oxide is 20 nm, the average particle size of the flake graphite is 0.5 μm, and the solvent is NMP; the mass ratio of the flake graphite, the nano copper oxide and the solvent is 1:5:100.
[0056] Example 2
[0057] A method for preparing a graphene-enhanced tellurium-copper composite material comprises the following steps:
[0058] (1) Tellurium copper powder, ethanol and graphene suspension are mixed and stirred at a speed of 300 r / min for 2 h to obtain a mixture; the mass percentage of tellurium in the tellurium copper powder is 0.3%; the average particle size of the tellurium copper powder is 34 μm; the mass ratio of the tellurium copper powder, ethanol and graphene suspension is 4:2:1; the graphene suspension is the graphene suspension prepared in Example 1;
[0059] (2) thermally reducing the mixture obtained in step (1), and then cooling it to room temperature in nitrogen to obtain a mixed powder; the thermal reduction temperature is 300° C., the thermal reduction time is 4 h, and the thermal reduction atmosphere is hydrogen;
[0060] (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material; the pressing method is cold isostatic pressing, the pressing pressure is 300 MPa, and the pressing time is 50 s; the sintering temperature is 950° C., the sintering time is 4 h, the sintering atmosphere is nitrogen, and the sintering cooling method is furnace cooling; the extrusion temperature is 800° C., the extrusion ratio is 30, and the extrusion atmosphere is nitrogen.
[0061] Example 3
[0062] A method for preparing a graphene suspension comprises: mixing flake graphite, nano copper oxide and a solvent, and then performing ultrasonic exfoliation at a power of 300 W for 12 hours to obtain a graphene suspension;
[0063] The average particle size of the nano copper oxide is 20 nm, the average particle size of the flake graphite is 20 μm, and the solvent is NMP; the mass ratio of the flake graphite, the nano copper oxide and the solvent is 1:10:100.
[0064] Example 4
[0065] A method for preparing a graphene-enhanced tellurium-copper composite material comprises the following steps:
[0066] (1) Tellurium copper powder, ethanol and graphene suspension are mixed and stirred at a speed of 200 r / min for 2 h to obtain a mixture; the mass percentage of tellurium in the tellurium copper powder is 0.7%; the average particle size of the tellurium copper powder is 30 μm; the mass ratio of the tellurium copper powder, ethanol and graphene suspension is 10:2:1; the graphene suspension is the graphene suspension prepared in Example 3;
[0067] (2) thermally reducing the mixture obtained in step (1), and then cooling it to room temperature in nitrogen to obtain a mixed powder; the thermal reduction temperature is 320° C., the thermal reduction time is 4 h, and the thermal reduction atmosphere is hydrogen;
[0068] (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material; the pressing method is cold isostatic pressing, the pressing pressure is 280 MPa, and the pressing time is 60 s; the sintering temperature is 1080° C., the sintering time is 5 h, the sintering atmosphere is nitrogen, and the sintering cooling method is furnace cooling; the extrusion temperature is 950° C., the extrusion ratio is 150, and the extrusion atmosphere is nitrogen.
[0069] Example 5
[0070] A method for preparing a graphene suspension comprises: mixing flake graphite, nano copper oxide and a solvent, and then performing ultrasonic exfoliation at a power of 400 W for 8 hours to obtain a graphene suspension;
[0071] The average particle size of the nano copper oxide is 20 nm, the average particle size of the flake graphite is 10 μm, and the solvent is NMP; the mass ratio of the flake graphite, the nano copper oxide and the solvent is 1:7:100.
[0072] Example 6
[0073] A method for preparing a graphene-enhanced tellurium-copper composite material comprises the following steps:
[0074] (1) Tellurium copper powder, ethanol and graphene suspension are mixed and stirred at a speed of 100 r / min for 2 h to obtain a mixture; the mass percentage of tellurium in the tellurium copper powder is 0.7%; the average particle size of the tellurium copper powder is 40 μm; the mass ratio of the tellurium copper powder, ethanol and graphene suspension is 8:2:1; the graphene suspension is the graphene suspension prepared in Example 5;
[0075] (2) thermally reducing the mixture obtained in step (1), and then cooling it to room temperature in nitrogen to obtain a mixed powder; the thermal reduction temperature is 300° C., the thermal reduction time is 3 h, and the thermal reduction atmosphere is hydrogen;
[0076] (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material; the pressing method is cold isostatic pressing, the pressing pressure is 400 MPa, and the pressing time is 40 s; the sintering temperature is 1000° C., the sintering time is 5 h, the sintering atmosphere is nitrogen, and the sintering cooling method is furnace cooling; the extrusion temperature is 850° C., the extrusion ratio is 100, and the extrusion atmosphere is nitrogen.
[0077] Comparative Example 1
[0078] A method for preparing a graphene-enhanced tellurium-copper composite material comprises the following steps:
[0079] (1) Tellurium copper powder, ethanol and graphene suspension are mixed and stirred at a speed of 300 r / min for 2 hours to obtain a mixture; the mass percentage of tellurium in the tellurium copper powder is 0.3%; the average particle size of the tellurium copper powder is 34 μm; the mass ratio of the tellurium copper powder, ethanol and graphene suspension is 4:2:1; the preparation method of the graphene suspension is: flake graphite and NMP are mixed, and then ultrasonically exfoliated at a power of 500 W for 4 hours to obtain a graphene suspension, the average particle size of the flake graphite is 0.5 μm, and the mass ratio of the flake graphite to NMP is 1:100;
[0080] (2) thermally reducing the mixture obtained in step (1), and then cooling it to room temperature in nitrogen to obtain a mixed powder; the thermal reduction temperature is 300° C., the thermal reduction time is 4 h, and the thermal reduction atmosphere is hydrogen;
[0081] (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material; the pressing method is cold isostatic pressing, the pressing pressure is 300 MPa, and the pressing time is 50 s; the sintering temperature is 950° C., the sintering time is 4 h, the sintering atmosphere is nitrogen, and the sintering cooling method is furnace cooling; the extrusion temperature is 800° C., the extrusion ratio is 30, and the extrusion atmosphere is nitrogen.
[0082] The properties of the graphene-enhanced tellurium-copper composite materials prepared in Examples 2, 4, 6 and Comparative Example 1 were tested, and the results are shown in Table 1:
[0083] Table 1 Properties of graphene-enhanced tellurium-copper composite materials prepared in Examples 2, 4 and 6
[0084]
[0085]
[0086] Among them, the test standard for conductivity is: GB-5586 Basic performance test method for electrical contact materials;
[0087] The test standard for tensile strength is: GB 228.1 Tensile test for metallic materials Part 1 Room temperature test method;
[0088] The test standard for the limiting current breaking number is: TZZB 1024-2019 High-voltage DC relays for electric vehicles.
[0089] It can be seen from Table 1 that after the graphene suspension is prepared by the method provided by the present invention, the electrical conductivity, tensile strength and limiting current breaking times of the graphene enhanced tellurium copper composite material prepared by the graphene suspension are significantly improved, among which the tensile strength and limiting current breaking times are greatly improved, indicating that the graphene suspension provided by the present invention can improve the mechanical properties and electrical properties of the graphene enhanced tellurium copper composite material.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a graphene suspension, comprising: flake graphite, nano copper oxide and solvent are mixed, and then ultrasonically exfoliated to obtain a graphene suspension; The average particle size of the nano copper oxide is 1 to 50 nm.
2. The preparation method according to claim 1, characterized in that: The average particle size of the flake graphite is 0.5 to 20 μm.
3. The preparation method according to claim 1, characterized in that: The solvent is NMP.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the flake graphite, nano copper oxide and solvent is 1:(5-10):(80-120).
5. The graphene suspension prepared by the preparation method according to any one of claims 1 to 4.
6. A method for preparing a graphene-enhanced tellurium-copper composite material, comprising the following steps: (1) mixing tellurium copper powder, ethanol and a graphene suspension to obtain a mixture; the graphene suspension is a graphene suspension prepared by the preparation method according to any one of claims 1 to 4 or a graphene suspension according to claim 5; (2) subjecting the mixture obtained in step (1) to thermal reduction to obtain a mixed powder; (3) The mixed powder obtained in step (2) is pressed, sintered and extruded in sequence to obtain a graphene-reinforced tellurium-copper composite material.
7. The preparation method according to claim 6, characterized in that: In the step (1), the mass percentage of tellurium in the tellurium copper powder is 0.1-1%, and the average particle size of the tellurium copper powder is 10-40 μm.
8. The preparation method according to claim 6, characterized in that: In the step (1), the mass ratio of tellurium copper powder, ethanol and graphene suspension is (4-10):2:
1.
9. The preparation method according to claim 6, characterized in that: The temperature of the thermal reduction in step (2) is 280-320° C., the time of the thermal reduction is 2-4 hours, and the atmosphere of the thermal reduction is hydrogen.
10. The graphene-reinforced tellurium-copper composite material prepared by the preparation method according to any one of claims 6 to 9.